Site-dependent differences in both prelamin A and adipogenic genes in subcutaneous adipose tissue of patients with type 2 familial partial lipodystrophy. Issue 1 (19th September 2008) - Araújo-Vilar, D; Lattanzi, G; González-Méndez, B; Costa-Freitas, A T; Prieto, D; Columbaro, M; Mattioli, E; Victoria, B; Martínez-Sánchez, N; Ramazanova, A; Fraga, M; Beiras, A; et al.
Abstract : Background: Type 2 familial partial lipodystrophy (FPLD2) is characterised by loss of fat in the limbs and buttocks and results from mutations in the LMNA gene. Aim: To evaluate the role of several genes involved in adipogenesis in order to better understand the underlying mechanisms of regional loss of subcutaneous adipose tissue (scAT) in patients with FPLD2. Methods: In total, 7 patients with FPLD2 and 10 healthy control participants were studied. A minimal model was used to calculate the insulin sensitivity (IS). scAT was obtained from abdomen and thigh by biopsy. Relative gene expression was quantified by real-time reverse transcription PCR in a thermal cycler. Prelamin A western blot analysis was carried out on scAT and prelamin A nuclear localisation was determined using immunofluorescence. Adipocyte nuclei were examined by electron microscopy. Results: Patients with FPLD2 were found to have significantly lower IS. The expression of LMNA was similar in both groups. The expression of PPARG2, RB1, CCND3 and LPL in thigh but not in abdomen scAT was significantly reduced (67%, 25%, 38% and 66% respectively) in patients with FPLD2. Significantly higher levels of prelamin A were found in peripheral scAT of patients with FPLD2. Defects in the peripheral heterochromatin and a nuclear fibrous dense lamina were present in the adipocytes of patients with FPLD2. Conclusions: In FPLD2 participants, prelamin A accumulation in peripheral scAT is associated with a reduced expression of several genes involved in adipogenesis, which could perturb the balance between proliferation and differentiation in adipocytes, leading to less efficient tissue regeneration.